Connecting with prospective medical tourists online: A cross-sectional analysis of private hospital websites promoting medical tourism in India, Malaysia and Thailand. (February 2017) - Moghavvemi, Sedigheh; Ormond, Meghann; Musa, Ghazali; Mohamed Isa, Che Ruhana; Thirumoorthi, Thinaranjeney; Bin Mustapha, Mohd Zulkhairi; Kanapathy, Kanagi A./P.; Chiremel Chandy, Jacob John
Abstract: Websites of private hospitals promoting medical tourism are important marketing channels for showcasing and promoting destinations' medical facilities and their array of staff expertise, services, treatments and equipment to domestic and foreign patient-consumers alike. This study examines the websites of private hospitals promoting medical tourism in three competing Asian countries (India, Malaysia and Thailand) in order to look at how these hospitals present themselves online and seek to appeal to the perceived needs of (prospective) medical tourists. The content and format of 51 hospitals are analyzed across five dimensions: hospital information and facilities, admission and medical services, interactive online services, external activities, and technical items. Results show differences between Indian, Malaysian and Thai hospital websites, pointing to the need for hospital managers to improve their hospitals' online presence and interactivity. Highlights: Websites of private hospitals promoting medical tourism in India, Malaysia and Thailand is examined. The content and format of 51 hospitals across five dimensions analyzed. Results provide pointers for hospital managers to improve their online presence.